Synthesis and Characterization of Au:CuO Nanocomposite by Laser Soldering on Porous Silicon for Photodetector - Rashed, Halah H; Moatasemballah, Juhaina (Al-Nahrain Journal of Science, 2017)
This work aimed to the synthesize of composite Au:CuO (NPs) by pulsed laser soldering process. The optical properties, stability, structural properties and surface morphology of Au:CuO nanocomposite were characterized by UV–VIS spectrophotometer, Zeta potential measurement, XRay Diffraction pattern and Atomic Force Microscope respectively. The band gap of Au doped CuO is about 1.95 eV. The amount of zeta potential is -54 mV, its indicating that the negatively charged of Au: CuO nanocomposite in deionized water and the colloid is good stability against aggregation. Surface morphology of Au:CuO nanocomposite show a large number of particles have diameter about 55nm. Au: CuO nanocomposite deposited on porous silicon by drop casting technique for preparation of silicon photodetector, the electrical properties prove that band gap alignment between Au: CuO nanocomposite and PS facilitates the electron transfer and further increases the photoresponsitivity and Quantum efficiency.